Leadership, Innovation and Performance in Portuguese Hotel Sector - Leitão, Cláudia Ferreira (2023)
Leadership, innovation, and performance are essential factors to achieve the desired sustainable profitability of companies. The relationship between these variables is one of the keys to the organizational success, although their study has proved to be complex. The purpose of this article is to analyse the impact of leadership on the relationship between innovation and performance in the Portuguese hotel sector. To answer to this challenge, a survey was carried out to top and middle managers of four-star and ve-star hotel units. The existence of a positive correlation between innovation and performance was found; however, leadership has not been shown to have a moderating effect on the relationship. The work highlights several important contributions to the hotel industry and identi- fies aspects that, when well implemented and developed, can lead to better performance in organizations.